The Influence of Locus of Control, Professional Ethics and Client Narcissism on Audit Judgement (Empirical Study on East Jakarta Public Accounting Firm) - Kemalasari, Novawiguna; Putriranti, Reyfira; Putra, Yananto Mihadi; Pratiwi, Riri (Baca Dulu Publisher, 2025)
Audit judgement by auditors is a crucial element in determining the fairness of the company's financial statements. The quality of audit judgement can be influenced by various factors, including technical factors such as the limited time and environment of the audit as well as non-technical factors such as the behavior and character of individual auditors. Seeing this phenomenon, special attention is needed to factors that are suspected of influencing the auditor's decision-making process, both internal auditor factors such as Locus of Control and Professional Ethics, as well as external factors from the client's side in the form of Client Narcissism. This study aims to determine the influence of these factors on the quality of audit judgment, especially for auditors at Public Accounting Firms (KAP) in the East Jakarta region. This study uses a quantitative approach with data analysis using Partial Least Square (PLS) through the SmartPLS 3.0 application. The research sample consisted of 74 auditors working at KAP East Jakarta, who were selected based on the criteria of a minimum of 1 year of experience and a minimum of S1 education. The results of the study show that Professional Ethics has a positive and significant effect on Audit Judgment, meaning that the better the application of ethics by the auditor, the better the quality of the audit judgement produced. However, Locus of Control and Client Narcissism did not show a significant influence on audit judgment. These findings suggest that auditors' self-control attitudes and client character do not significantly affect the quality of audit considerations. Based on the results of the study, Professional Ethics has a significant influence on the quality of audit judgment, while Locus of Control and Client Narcissism have no significant effect.